Pengaruh Social Media Marketing Activities terhadap Brand Trust dan Brand Image pada Purchase Intention di E-Commerce pada Generasi Z - Khairunnisa; Barika Gumay (MES Management Journal, 2025)
The rapid growth of e-commerce in Indonesia has transformed consumer behavior, particularly among Generation Z as the most active digital users. This study aims to investigate the effect of social media marketing activities (SMMA) on brand trust and brand image and their subsequent impact on purchase intention. A quantitative descriptive-causal design was applied, using purposive sampling with 140 respondents from Generation Z in the Greater Jakarta (Jabodetabek) area. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that SMMA positively influences brand trust and brand image, which in turn enhance purchase intention. These results highlight the importance for e-commerce businesses to implement effective social media strategies that build trust and a positive brand image among Generation Z.